(untitled) (Islamic Sciences Journal, 2023)
The research deals with the symbolism of the sword in Al-Talafari poetry, which I tried to shed light on its aesthetics, and its good use in the poetic text, and I tried to highlight the dimensions of the symbol in its references, philosophy and image that were woven and employed in poetic texts in this era. I traced back the good employment of the poet who was chosen for his Aesthetic, artistic brightness, completeness of good photography in the depth of poetic texts that were the link between the past and the present, and the reflection of the historical and color legacy on the shadows of the poetic experience that poets were going through, The poet depicted their psychological emotions and their apocalyptic recession with what was going on around them from occasions and tribulations, which cast a shadow on their poetic experiences that varied in drawing their reality and their social emotion, They invoked the war symbols to deepen the link with reality and consolidate the idea in the soul of the recipient, The use of symbols in the poetic text makes it more aesthetic and clear so that the symbolic image in all its parts settles in the mind of the recipient.